Pendanaan Pembangunan Ekonomi Indonesia Melalui Sukuk Negara Ritel: Analisis Hukum Ekonomi Islam - Kurniawan, Taufiq (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
Sukuk Ritel (SR) is one of the sovereign sukuk whose main purpose is to fund economic development, especially infrastructure development. To accelerate infrastructure development, the government issued Sukuk Ritel in 2009 as a funding source. This study was conducted to determine how the law of economic development funding in Indonesia sourced from Sukuk Ritel is viewed from the perspective of Islamic economic law. Data was collected through a literature review which was then analyzed using a normative approach. The results of this study indicate that borrowing or funding for infrastructure development through Sukuk Ritel is legally permissible (mubah), and Sukuk Ritel is better than borrowing directly. However, the government needs to continue taking precautionary steps when the state debt is approaching the normal threshold for borrowing funds.